THE SUPERIORITY OF LEADERSHIP IN ISLAMIC EDUCATION INSTITUTIONS AT MADRASAH ALIYAH IN JAMBI PROVINCE - Mukhlis; Pendi, Hamdi Zas; Tabroni; Suryani, Dewi (International Journal of Education, Language, and Social Science, 2024)
Developing leadership in Madrasah Aliyah (MA) requires a deep understanding of these institutions' unique characteristics and context. This study, conducted in Jambi Province using a qualitative approach, aims to examine the leadership superiority in MA. The primary goal is to gather scientific data to improve leadership practices. The research findings indicate that effective leadership development demands tailored strategies and actions specific to the context of these institutions. Meanwhile, the results of this research show that developing leadership superiority in MA requires specific understanding and actions according to the characteristics and context of this Islamic educational institution. Additionally, the head of the madrasas have taken steps to develop leadership superiority in Islamic educational institutions in Madrasah Aliyah, Jambi province.